Development prospects of town Rehau/Oberfranken – a contribution to applied urban geography - Maier, Jörg; Kadner, Beate; Gutgesell, Matthias (Journal for Geography, 2006)
The attempt of a classification or allocation of functions for provincial towns reveals a exceedingly wide spectrum of manifestations, structures and perspectives. The palette ranges from examples showing traditional provincial structures with decreasing population and economic power to the "vital cities”, which came out with the EU competition. Localized in the environs of the Metropolises they are characterized by high communication dynamism and an highly attractive social environment. The successful industrial town Rehau situated in the rural space on the border to Czech Republic with the new development possibilities also belongs to this category. A huge number of geographic research projects prove that the common prejudice of the small town´s provincial fug - cultivated in particular of the metropolitan press - is not appropriate. However, other studies concerning the subject and finding further evidence will be necessary for the purpose of a resurgence of the geographic provincial town research.